Kejadian Dermatosis yang Tinggi pada Anjing Jalanan di Bali (A HAIGH DERMATOSIS INCIDENCE AMONG STRAY DOGS IN BALI) - Wiryana, I Kadek Saka; Damriyasa, I Made; Dharmawan, Nyoman Sadra; Arnawa, Kadek Agus Agra; Dianiyanti, Kadek; Harumna, Dina (Jurnal Veteriner, 2014)
This study was designed to investigate the incidence of dermatosis among stray dogs in Bali. A totalof 401 stray dogs collected in the animal shelter of Bali Animal Welfare Association during 2011 wasinvestigated in this study. Dogs were examined by the clinical sign and continued by skin scraping, cytologyand wood lamp examination. In total, 37,9% sample were positive for dermatosis. Bacterial causeddermatosis found to be the most prevalent (23,6%), followed by tick and fleas (16.5%), scabies (12.7%),malassezia (8.2%), demodek (8%) and ringworm (4.5%) respectively. We also found that dermatosis weremore prevalent in male dogs (50.9%) rather than female dogs (32.9%). Dogs 9-12 weeks old were moreheavily infected (45.8%) than other group. In conclusion, the incidence of dermatosis among stray dogs inBali is relatively high. This may need serious awareness as some of this dermatosis were zoonotic tohuman.
Keywords: dermatosis, stray dog, Bali